Changes in circulating vitamin D levels with loss of adipose tissue. Issue 6 (November 2016) - Gangloff, Anne; Bergeron, Jean; Lemieux, Isabelle; Després, Jean-Pierre
Abstract : Purpose of review: Low vitamin D levels have been extensively reported in obesity. Thus, the pandemic of obesity has been paralleled by a high prevalence of low vitamin D status. Given the well documented associations linking poor vitamin D status to adverse health outcomes (diabetes, cardiovascular disease, cancers, all-cause mortality), a proper understanding of the mechanisms linking excess adiposity to low vitamin D status is key to identify and implement effective interventions to replenish vitamin D levels in obese individuals. In this review, we will discuss recent literature investigating the effects of adipose tissue volume loss through energy restriction and/or physical activity on circulating 25-hydroxyvitamin D [25(OH)D] levels. Recent findings: Improvements of circulating 25(OH)D levels with adiposity loss through lifestyle interventions without supplementation is being reported by a growing number of studies, including recent randomized controlled trials. Summary: Low 25(OH)D is one of the metabolic disturbances associated with excess adiposity, particularly visceral adiposity. Recommendations for the treatment of obesity-related vitamin D deficiency should emphasize the role of visceral adiposity loss through healthy lifestyle habits, in conjunction with weight-adjusted vitamin D supplementation, not only to replenish 25(OH)D levels but also to address other visceral adiposity-related disturbances, such as insulin resistance, inflammation, hypertension, and dyslipidemia.